Sementes da esperança: floresce a Santa Religião em solo catarinense: elementos formadores do messianismo no Contestado - Almeida Júnior, Jair de (2010)
The Contestado War, 1912-1916, was a guerrilla war for lands between settlers and landowners. It was a phenomenon sparked by social causes, and feasible by religious reasons. At the beginning of 20th century, at the West of Santa Catarina state, monarchic ideas were predominant. Within the context of a recent Brazilian Republic proclaimed, politics started dividing an occupied land by subsistence farm workers. In addition, a railroad connecting São Paulo to Santa Maria, in Rio Grande do Sul state was been built by a north-American Brazil Railway Company. According to an agreement, the company obtained from the government the right to explore a strip of land 15 km wide on each side of the railroad. The concession guaranteed also the opening of a company to extract rich wood throughout Santa Catarina West. This means that subsistence farm workers were suddenly driven out from their lands. The name Contestado refers to an inland region contested by the States of Paraná and Santa Catarina, prompting the spirits to war. Previous to this social caos, the Contestado received influence from three monks in the region. The first, João Maria de Agostini. He was a devout to Saint Anthony, who wandered as a healer and miracle performer. The second appeared right after João Maria, who also adopted the alias of João Maria, although his real name was Atanás Marcaf. He walked in the same path as his predecessor, but having his own nuances. Marcaf was seen as someone supporting the Federalist Revolution. The third monk, José Maria, self-proclaimed João Maria´s brother, attract to himself people's admiration and confidence. The first two ones preferred a nomad and lonely life, whereas the third had many followers and became even a military leader. José Maria was killed in combat, and his followers settle themselves politically and religiously. Soon their leadership became intimidation. As a result of visions the virgenato and the meninos-deus are established. They were groups who were receiving direction straight from José Maria. We can realize religious elements from Africa and from native Indians in this kind of messianic movement amidst the Contestado. Of course, all of these were blended within a popular Catholic Church environment. Generally speaking, this last group gave rise to an embrionary model of local animism and possession of spirits. Specifically, their contribution in the religious scenario was with rites, beliefs and ceremonies. A constant resistance from the subsistence farm workers brought over them a military intervention. Federal troops, supported by local cowboys, were sent to the region to crush the rebellion. Close to the end of the war the religious feeling started being supplanted by a kind of barbarian behavior. As a result the South of Brazil experiences a religious legacy of reverence to João Maria in the popular Catholicism of three South states. This legacy goes beyond, reaching the Kaingangs, a native American ethnic group, and even contemporary minority movements as MST.